2021
DOI: 10.1002/mop.33094
|View full text |Cite
|
Sign up to set email alerts
|

An injection‐locked green InGaN diode laser

Abstract: We designed a single-frequency green laser system that can deliver a 60-mW frequency-tunable single-longitudinal-mode laser beam, having a 6.5 MHz linewidth at around 519 nm. An external cavity diode laser can provide a wavelength-tunable single frequency laser beam, but its output power is limited. Therefore, an injection-locked laser was designed with a Fabry-Perot type green InGaN laser diode in an external Littrow-type cavity as the master laser and another laser diode of the same model as the slave laser.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Lu et al also reported a kind of self-frequency-doubling (SFD) crystal combing the processes of fundamental production and second harmonic generation, with prospects of high-power applications [10]. [9] SHG + SFG 514 nm (~) 290 mW 36% Lu et al [10] SFD 513 nm (~) 6.2 W 30% Chi et al [6] ECDL 515 nm (9.2 nm) 480 mW ~~0.5 nm Mateus et al [7] micro-ring 520 nm (6.0 nm) 10.75 mW ~26 kHz Chen et al [11] injection-lock 519 nm (~) 60 mW ~6.5 MHz Tawfieq et al [ In this paper, we present a 200 mW narrow linewidth laser at 510 nm for the study of Cs Rydberg atoms. To achieve this, we have established an ultra-narrow linewidth laser operating in the telecom band (1530 nm) as the seed source.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al also reported a kind of self-frequency-doubling (SFD) crystal combing the processes of fundamental production and second harmonic generation, with prospects of high-power applications [10]. [9] SHG + SFG 514 nm (~) 290 mW 36% Lu et al [10] SFD 513 nm (~) 6.2 W 30% Chi et al [6] ECDL 515 nm (9.2 nm) 480 mW ~~0.5 nm Mateus et al [7] micro-ring 520 nm (6.0 nm) 10.75 mW ~26 kHz Chen et al [11] injection-lock 519 nm (~) 60 mW ~6.5 MHz Tawfieq et al [ In this paper, we present a 200 mW narrow linewidth laser at 510 nm for the study of Cs Rydberg atoms. To achieve this, we have established an ultra-narrow linewidth laser operating in the telecom band (1530 nm) as the seed source.…”
Section: Introductionmentioning
confidence: 99%